ASSESSMENT OF THE NUTRITIONAL AND HEALTH STATUS OF WOMEN ENTREPRENEURS IN FOOD PROCESSING UNITS IN TIRUPATI REGION - T. DEVI; K SASI; Dr. V. BINDU (The Bioscan, 2024)
Food and Apparels are the fundamental needs of every human being. Present in our society every one spending a lot of money for good food and fashionable clothes because of this reason the demand is growing day by day. There is a never ending demand and have a many opportunities from young to old people. Business can be started with less investment in food sector. Hence, many people showing interest to start small enterprises. And especially women are entering into entrepreneurship to earn money for solving their family and financial problems. In this journey they are facing many problems related to work and family, some-times they are not able to balance their work and family life. Because of busy timings, self- cooking and serving most of the women entrepreneurs were skipping or eating their meals very lately. Hence, they were suffering with nutritional and health related issues. Major factor was standing in front of fire for long time was affecting on their health. Female entrepreneurs face many obstacles, ranging from limited access to finance and markets to social norms and regulatory blocks. This research paper aims to explore the role of women entrepreneurs in food processing units. It investigates the challenges faced by women when starting and growing their enterprises and evaluates strategies designed to combating their problems. The paper emphasized their role in economic growth and also discussed the various obstacles faced by women entrepreneurs, including financial constraints, limited access to markets, limited support from family nutritional and health related issues etc.